The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/ja304971e
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Volatile Organic Compounds at the Surface of a Water Droplet

Abstract: Knowledge of the role of water droplets and aerosols in atmospheric chemistry is crucial to significantly improve our understanding of global warming and air quality. Chemistry at the air/water interface, in particular, is still poorly understood. There is a great need to understand how clouds and aerosols process chemistry of organics prevalent in the atmosphere. We report in this study the first computer simulation of a volatile organic compound (formaldehyde) at the air/water interface with explicit descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 76 publications
8
72
0
Order By: Relevance
“…Interestingly, this proposed mechanism for the chemistry of MA at the air/liquid water interface also suggests a new source for NH 2 radicals at aerosol surfaces, other than by reaction of absorbed NH 3 . This provides important support for the recent work of Martin-Costa et al 77 and Zhong et al 68 on the interaction of NH 2 radical and volatile organic compounds at the surface of water droplet. Future work is planned to examine the influence of both temperature and humidity on the position/orientation of such by-products at aerosol droplets.…”
Section: F Chemistry Implications Of Ma At the Interfacesupporting
confidence: 78%
See 2 more Smart Citations
“…Interestingly, this proposed mechanism for the chemistry of MA at the air/liquid water interface also suggests a new source for NH 2 radicals at aerosol surfaces, other than by reaction of absorbed NH 3 . This provides important support for the recent work of Martin-Costa et al 77 and Zhong et al 68 on the interaction of NH 2 radical and volatile organic compounds at the surface of water droplet. Future work is planned to examine the influence of both temperature and humidity on the position/orientation of such by-products at aerosol droplets.…”
Section: F Chemistry Implications Of Ma At the Interfacesupporting
confidence: 78%
“…Methylamine belongs to a class of organics referred as amphiphilic organics, which are known to be partitioned at the interface creating a hydrophobic film on an aqueous aerosol 73,74 and determining many chemical properties of aerosols. Recent experimental and theoretical research [75][76][77] has shown that atmospheric reactions of organic molecules can be enhanced on a surface compared to the gas phase. As will any surface active molecule, amphiphilic organics will reduce the surface tension of water, affecting the droplet growth and trace-gas uptake, finally determining the reactivity towards oxidative gases and the ability of the aerosol to absorb or scatter radiation.…”
Section: F Chemistry Implications Of Ma At the Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…This molecule exhibits a preference for the interface that is about 3 kcal mol −1 with respect to bulk water, not far from the value 2.8 kcal mol −1 reported earlier by Canneaux et al 15 The result for formaldehyde (1.5 kcal mol −1 ) reproduces the value reported before using QM/MM simulations. 2 It is interesting to point out that the affinity for the air water interface increases in the order formaldehyde < acetaldehyde < benzaldehyde (compare the stabilisation at the interface with respect to the gas phase), which parallels the increasing hydrogen-bond acceptor character of the compounds. It also parallels the increasing polarity of the carbonyl group in the three aldehydes (see below).…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] For instance, the rate and mechanism by which VOCs adsorb and react onto water droplets or surface of aerosol particles will dictate how far and fast these pollutants can be transported in the atmosphere. This capability of monitoring adsorption mechanisms and adsorption kinetics under ambient condition will be particularly useful in characterizing the adsorption of atmospheric pollutants, such as VOCs, to the air/aqueous interface.…”
Section: Discussionmentioning
confidence: 99%